The Fecal Microbiota in the Domestic Cat (Felis catus) Is Influenced by Interactions Between Age and Diet; A Five Year Longitudinal Study - Bermingham, Emma N.; Young, Wayne; Butowski, Christina F.; Moon, Christina D.; Maclean, Paul H.; Rosendale, Douglas; Cave, Nicholas J.; Thomas, David G. (Frontiers in Microbiology, 2018)
In humans, ageing is associated with changes in the gastrointestinal microbiota; these changes may contribute to the age-related increase in incidence of many chronic diseases, including Type 2 diabetes. The life expectancies of cats are increasing, and they are also exhibiting the same types of diseases. While there are some studies investigating the impacts of diets on gastrointestinal microbiota in young cats, the impacts of ageing in older cats has not been explored. We followed a cohort of related kittens, maintained on two commercial diets (kibbled and canned) from weaning (8 weeks) to 5 years of age (260 weeks). We hypothesised that the long-term feeding of specific diet formats would (a) lead to microbial composition changes due to ageing, (b) impact body composition and (c) affect insulin sensitivity in the ageing cat. We observed that both diet and age affected the faecal microbial composition, and while age correlated with changes in body composition and insulin sensitivity, diet did not. 16SrRNA sequencing found Unclassified Peptostreptococcaceae were prominent across all ages averaging 21.3% of gene sequence reads and were higher in cats fed canned diets (average of 25.7 % of gene sequence reads, vs 17.0% for kibbled). Age-related effects on body composition and insulin sensitivity may become apparent as the cats grow older; this study will continue to assess these parameters.